Electroacupuncture Promotes Neural Proliferation in Hippocampus of Perimenopausal Depression Rats via Wnt/β-Catenin Signaling Pathway - Qin Jing (Journal of Acupuncture & Meridian Studies, 2020)
Background and Objective: Perimenopausal depression is caused by the impaired function of the ovarium before menopause and with a series of symptoms. Electroacupuncture (EA) therapy has been demonstrated to improve clinically depression. However, the mechanism underlying its therapeutic activity remains unknown. This study aimed to investigat the effects of EA treatment on the hippocampal neural proliferation through Wnt signaling pathway. Methods: Chronic unpredictable mild stress (CUMS) combined with bilateral ovariectomy (OVX) were used to establish a rat model of perimenopausal depression. The open field test (OFT) and sucrose preference test (SPT) were used to assess depression-like behaviors in rats. ELISAs were used to measure estrogen (E2), luteinizing hormone (LH) and gonadotropin-releasing hormone (GnRH) levels in the serum. RT-PCR and Western blot assay were utilized for measuring the mRNA expressions and protein expressions of GSK-3β/β-catenin. Results: Four-week EA treatment at three points including “Shenshu” (BL23), “Baihui” (GV20) and “Sanyinjiao” (SP6) simultaneously ameliorated depression-like behaviors in rats with CUMS and OVX, whereas rescued the decreased serum level of E2 and prevented the increased serum levels of GnRH and LH. EA treatment ameliorated CUMS and OVX-induced alterations of glycogen synthase kinase-3β (GSK-3β) and β-catenin mRNA levels, β-catenin and phosphorylated β-catenin (p-β-catenin) protein levels. Conclusions: The results showed that EA treatment promoted hippocampal neural proliferation in perimenopausal depression rats via activating the Wnt/β-catenin signaling pathway, indicating that EA may represent an efficacious therapy for perimenopausal depression.